1995
DOI: 10.4319/lo.1995.40.1.0094
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of passive accumulation of marine bivalve larvae on filamentous epibenthic structures

Abstract: A series of multifactorial experiments were carried out, in the field and in a flume, to test the hypothesis that early recruitment of semimobile bivalve spat on an epibenthic filamentous substratum is directly related to the heterogeneity (branching pattern) and the diameter of their individual branches or filaments and to evaluate the likelihood that passive settlement processes influence bivalve larval early recruitment on filamentous natural epibenthic substrata. The experiments were carried out with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 25 publications
1
78
1
Order By: Relevance
“…From these parameters, one can es- Table 3. Capture efficiencies computed from data collected by Harvey et al (1995). Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From these parameters, one can es- Table 3. Capture efficiencies computed from data collected by Harvey et al (1995). Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is useful to consider how capture efficiency varies across collector size, d c , given a fixed value Harvey et al (1995) in flume experiments simulating larval settlement. Multiples of the above two-dimensional structure were assembled to make a three-dimensional branch structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This coincides with the work done by Ohtaka et al (2011) in an inland lake in Cambodia, Southeast Asia, where they also found small L. fortunei (1.96-12.7 mm) attached only to E. crassipes roots even though there were other macrophytes available. Several studies have demonstrated the importance of filamentous substrates such as aquatic macrophytes and filamentous algae in the settlement of larvae and juveniles of marine and freshwater bivalve species (Bayne, 1964;Ackerman et al, 1994;Cáceres-Martínez et al, 1994;Harvey et al, 1995;Folino-Rorem et al, 2006). Dreissena polymorpha pediveligers have shown to prefer filamentous substrates, such as aquatic plants (Lewandowski, 1982).…”
Section: Tab 2 Analysis Of Deviancementioning
confidence: 99%